Biogeographic historical legacies in the net primary productivity of Northern Hemisphere forests. (21st February 2020) - Conradi, Timo; Van Meerbeek, Koenraad; Ordonez, Alejandro; Svenning, Jens‐Christian
Abstract: It has been suggested that biogeographic historical legacies in plant diversity may influence ecosystem functioning. This is expected because of known diversity effects on ecosystem functions, and impacts of historical events such as past climatic changes on plant diversity. However, empirical evidence for a link between biogeographic history and present‐day ecosystem functioning is still limited. Here, we explored the relationships between Late‐Quaternary climate instability, species‐pool size, local species and functional diversity, and the net primary productivity (NPP) of Northern Hemisphere forests using structural equation modelling. Our study confirms that past climate instability has negative effects on plant functional diversity and through that on NPP, after controlling for present‐day climate, soil conditions, stand biomass and age. We conclude that global models of terrestrial plant productivity need to consider the biogeographical context to improve predictions of plant productivity and feedbacks with the climate system. Abstract : This study shows that Late‐Quaternary climate instability has negative effects on present‐day plant diversity and through that on the net primary productivity (NPP) of Northern Hemisphere forests. These historical legacies in NPP suggest that models of NPP should consider the biogeographical context to improve predictions, and that climate‐change driven extinctions in trees may lead to long‐lasting reductions in ecosystem productivity.